Network pharmacology-based analysis in determining the mechanisms of Huoxin pill in protecting against myocardial infarction - Jia He; Da Wo; En Ma; Qing Wang; Jinxiao Chen; Jun Peng; Weidong Zhu; Dan-ni Ren (Taylor & Francis Group, 2021)
Context Huoxin pill (HXP) is a commonly used TCM prescription for treatment of cardiovascular diseases. However, its mechanism in protecting against myocardial infarction (MI) remains unknown. Objective We performed a network pharmacology analysis to explore the bioactive ingredients, therapeutic effects, and mechanisms of HXP in protecting against MI. Materials and methods HPLC was used to identify major bioactive compounds, and overlap with MI target genes were visualised. 10-Week old C57BL/6 mice were randomly assigned as: Sham-operated control, MI + Phosphate buffered saline (PBS), and MI + HXP (3 mg/mL and 9 mg/mL) treatment groups, received oral gavage administration once every two-days starting from 1-week prior to MI, and subsequently MI models were established for one-week before sacrifice. Results AKT1, VEGFA, TNF and RELA were identified as core target proteins among eighty-five candidate bioactive compounds identified in HXP with overlapping MI-related genes. HXP protection against MI was mainly via regulation of inflammatory pathways, notably TNF signalling pathway. Mouse models of MI and cardiac myoblasts demonstrated that HXP improved MI-induced injury via improving regulation of inflammatory response. Discussion and conclusion Stellasterol, deoxycholic acid, kaempferol, and quercetin are important active compounds contained in HXP with anti-inflammatory properties in the therapeutic treatment of MI. Due to the straightforward nature and effectiveness of taking oral HXP medications, our findings provide a theoretical basis for the clinical application of HXP in treating patients with angina or myocardial ischaemia. Future research into the combination of surgical procedures or medications that restore blood flow together with HXP as supportive medication would be worthwhile.